Immune response of escherichiosis infected children with epstein-barr virus - Olkhovskyi, Yevhen (ScienceRise: Medical Science, 2018)
The aim of the study was to investigate the features of the immune response on Escherichiosis in children infected with EBV. Methods. The cellular and humoral links of the immune response, phagocytic activity of neutrophils in 84 early aged patients with Escherichiosis was performed, it included 28 children with persistent inactive (latent) EBV infection and 26 patients with active EBV infection. The control group consisted of 20 practically healthy children. Static processing of the obtained results was carried out by means of Excel and Statistica 6.0 applications. Results. Different pathogenetic mechanisms of development of Escherichiosis have been revealed depending on the activity of EBV infection. The presence of latent or active EBV infection in patient with Escherichiosis leads to inhibition of cellular immunity and intension of the humoral immune response, signs of over-strain of the functional activity of neutrophils in acute period; in the case of latent form of EBV infection – a decrease in the functional reserve of the oxygen-dependent mechanism of bactericidal neutrophils. At the period of early convalescence of the disease, the complete recovery of the above indicators in patients with EBV infection does not occur. Conclusions. The revealed changes in the immune response in patients with Escherichiosis infected with EBV should be taken into account for adequate treatment of these patients, as well as for medical observation at the stages of rehabilitation